Novel electron-deficient oligo(phenyleneethynylene) derivatives for molecular electronics. Issue 9 (3rd May 2018) - Kitouni, Rachid; Selvanathan, Pramila; Galangau, Olivier; Norel, Lucie; Ouarda, Brahmia; Rigaut, Stéphane
ABSTRACT: This work reports synthesis and characterizations of two new electron-poor "oligo(phenyleneethynylene) (OPE) type" molecular wires for fundamental studies of electron transport in molecular junctions. These OPE derivatives display three aromatic rings functionalized (i) with NO2 (OPN ) or fluorine (OPF ) groups on the central aryl core and (ii) with the requisite protected thiolate anchoring groups on the lateral rings at both ends. We show that the moderately effective Sonogashira couplings can give access to such rare electrodeficient molecules but are unfortunately associated with significant side reactions. We detail the choice of adequate reaction conditions to allow the recovery of suitable amounts of compounds bearing several strongly electron-withdrawing substituents on their central ring for further study of the physical properties. GRAPHICAL ABSTRACT: